Microaxial pump‐supported coronary surgery without CPB to optimize outcome in severely impaired left ventricles - Anna Kathrin Assmann; Merve Arik‐Doganay; Sebastian Waßenberg; Payam Akhyari; Artur Lichtenberg; Alexander Assmann (ESC Heart Failure)
Abstract Aims Cardiopulmonary bypass (CPB) is the standard approach for coronary artery bypass grafting (CABG) in advanced ischaemic cardiomyopathy. Microaxial pump support has been envisioned to allow for beating‐heart CABG without CPB (MPCAB), thereby avoiding CPB‐inherent complications. This study aims to compare the in‐hospital and follow‐up outcome of MPCAB versus CPB‐CABG in patients with severely impaired left ventricular function. Methods and results Eleven patients suffering from three‐vessel coronary artery disease with median ejection fraction of 27% and deemed appropriate for CABG according to a heart team decision underwent MPCAB (support up to 5.5 L/min). Propensity score matching generated a CPB‐CABG control group (n = 33). The primary endpoint was defined as death from any cause by the end of the follow‐up (up to 4 years). MPCAB enabled continuous intraoperative and postoperative haemodynamic stabilization and complete myocardial revascularization. After CPB‐CABG, additional mechanical circulatory support was required in 45.5% (vs. 9.1% in MPCAB; P = 0.0363). The follow‐up all‐cause mortality after MPCAB amounted to 0% (vs. 33.3% after CPB‐CABG; P = 0.0414; NNT = 3). MPCAB patients showed a significantly decreased occurrence of major adverse cardiovascular events (MACE: 0% vs. 39.4%; P = 0.0189). Conclusions MPCAB allows for complete surgical revascularization without the necessity of extracorporeal circulation in spite of severely impaired left ventricular function. This first comparative study on the outcome after MPCAB versus CPB‐CABG demonstrates a significantly decreased risk of death as well as MACE in MPCAB patients. The MPCAB concept expands the spectrum of patients eligible for CABG without CPB towards patients with severely impaired left ventricular function.